Does adherence to the Mediterranean diet have differential effects on brain health for those living within and outside of the Mediterranean region?. (20th December 2022) - Gregory, Sarah; Ritchie, Craig W.; Shannon, Oliver; Stevenson, Emma; Blennow, Kaj; Muniz‐Terrera, Graciela
Abstract: Background: The Mediterranean diet (MedDiet) is a primarily plant‐based eating pattern. High adherence to a MedDiet has been associated with a 10‐40% lower incidence of dementia. There is limited evidence exploring associations between the MedDiet and Alzheimer's disease (AD) pathology. Method: Our study explored cross‐sectional associations between MedDiet and AD outcomes in the European Prevention of Alzheimer's Dementia Longitudinal Cohort Study (EPAD LCS), comparing effects between those living within and outside of the Mediterranean region. After deriving MEDAS scores, to quantify adherence to the MedDiet, we used linear regression analyses to test for associations between the MedDiet and hippocampal volume, white matter lesion volume (WMLV) cerebrospinal fluid Abeta 1‐42 and phosphorylated tau and cognition. Participants were categorised by Mediterranean or non‐Mediterranean region according to European Union classification. Result: We included 1625 participants from the EPAD LCS baseline dataset, mean age 65.48 (±7.40) years, majority female (55.9%), majority with family history (66.3%) and minority APOEε4 carriers (39.0%). Mediterranean participants had higher MEDAS scores compared to non‐Mediterranean participants (7.44 (±1.60) vs 7.20 (±1.74), p = 0.007). Higher adherence to the MedDiet was associated with lower log WMLV in fully adjusted models (b: ‐0.06, standard error (SE): 0.02, p<0.001), indicating better brain health. Geographical region analysis found this effect only in Mediterranean participants (fully adjusted: b: ‐0.10, SE: 0.03, p<0.001). Exploratory analysis further showed this effect was only apparent in male, and not female, participants. For non‐Mediterranean participants, higher adherence to the MedDiet was associated with lower Four Mountains Test scores (fully adjusted: b: ‐0.25, SE: 0.08, p = 0.003), indicating poorer brain health. Analyses are corrected using the Benjamini‐Hochberg False Discovery Rate estimation. Conclusion: Our findings suggest that adherence to the MedDiet is associated with better brain health in those living within, but not outside of, the Mediterranean region. One explanation may be a difference in the duration of exposure to this diet (i.e., life‐long versus later life adoption in Mediterranean vs. non‐Mediterranean regions). This study highlights the need to further explore who the MedDiet is particularly effective for with regard to brain health outcomes, to better inform public health campaigns and patient level interventions.